Shaking Table Tests of Curved Bridge considering Bearing Friction Sliding Isolation - Lei Yan; Qingning Li; Chun Han; Haotian Jiang (Shock and Vibration)
Specific to severe damage to curved bridges in earthquakes caused by the excessive force of the fixed bearings and piers, a new seismic design method on curved bridges considering bearing friction sliding isolation is proposed in this paper. Seismic model bridge and isolation model bridge with similarity ratio of 1/20 were made and the shaking table comparison test was conducted. The experimental results show that the isolation model curved bridge suffered less seismic damage than the seismic model curved bridge. The fundamental frequencies of the seismic model bridge and isolation model bridge decreased and the damping ratio increased with the increase of seismic intensity. Compared with seismic curved bridge, the maximum reduction rates of peak acceleration along the radial and tangential directions on the top of pier of the isolation model curved bridge were 47.3% and 55.5%, respectively, and the maximum reduction rate of the peak strain on the bottom of pier of the isolation model curved bridge was 43.4%. For the isolation model curved bridge, the maximum reduction rate of peak acceleration on the top of pier was 24.6% compared with that on the bottom of pier. The study results can provide experimental basis for the seismic design of curved bridges.